PERSEPSI GUYUB TUTUR MANGGARAI TENTANG SIGNIFIKANSI HARMONI SOSIAL: ANALISIS LINGUISTIK KEBUDAYAAN - Bustan, Fransiskus; Sumitri, Ni Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2010)
This study examines the perception of Manggarai speech community (MSC) on the significance of social harmony in terms of cultural linguistics. In accordance with its problem, this study is descriptive-qualitative based on phenomenological philosophy. The methods and techniques of data collection are observation, interview, recording, note-taking, and documentation study. Data was analyzed qualitatively by using inductive method and encoding technique. The result of study shows, there are a number of traditional expressions in Manggarai language and culture conveying the perception of MSC on the significance of social harmony. In terms of the forms and meanings of linguistic phenomena used, such traditional expressions are the cultural oases inherited from the past functioning as moral and ethic guideline for MSC in maintaining social harmony. Recognizing the contents of those traditional expressions have been reduced out of function frame and meaning schema declared by their ancestors, such traditional expression should be documented, so that their social values be maintained according to real substances in the life of MSC nowadays and in the future.